Investigation of the Electrical Properties and Electromagnetic Shielding Effectiveness of Polypyrrole Coated Cotton Yarns - (:unkn) unknown (INST CHEMICAL FIBRES, 2013)
Polypyrrole (PPy) coated cotton yarns were prepared by the vapour phase polymerisation technique at various initiator concentrations. Iron (III) chloride (FeCl3) was used as the initiator at four different concentrations (0.2, 0.4, 0.6 & 0.8 mol/l) respectively. In this work, the effects of initiator concentration on the tensile, electrical and morphological properties of the cotton yarns were investigated. PPy coated cotton yarns were woven on a handloom for the investigation of electromagnetic shielding effectiveness. The fabric samples prepared were evaluated in terms of shielding behavior. Scanning electron microscopy (SEM) analysis showed that the yarn treated with 0.4 mol/l initiator concentration gave the most uniform PPy layer and highest shielding value. The existence of PPy was proved by using Fourier transform infrared spectroscopy (FTIR) analysis.
Keywords: polypyrrole; vapour phase polymerization; electrical property; electromagnetic shielding effectiveness; VAPOR-PHASE POLYMERIZATION; CONDUCTIVE POLYPYRROLE; COMPOSITES; FIBERS